Congenital hypothyroidism in Rieger Syndrome. (2nd January 2016) - Örnek, Nurgül; Oğurel, Reyhan; Örnek, Kemal
Abstract: Rieger syndrome (RS) is a multiple malformation syndrome characterized by ocular manifestations and extraocular defects. Herein, we report a 9-year-old boy who exhibited Rieger Syndrome phenotype as well as congenital hypothyroidism which may be an underappreciated feature of RS.